Implementing Learning from Excellence in a postanaesthesia care unit: a qualitative study of healthcare professionals’ experiences after six months - Gørill Birkeli; Ellen Catharina Tveter Deilkås; Randi Ballangrud; Anne Karin Lindahl (BMC Health Services Research)
Abstract Background Prevailing efforts to ensure patient safety have primarily focused on learning from errors and adverse events (Safety-I). However, it is advocated that complex systems also learn from success (Safety-II) and focus on healthcare professionals’ well-being at work to increase resilience. Learning from Excellence is a British initiative designed to learn from successful practices and provide positive feedback to the staff. It has gained enthusiastic followers in several countries, including Norway. However, how it influences learning, well-being and quality improvement, has not been studied in-depth. This study intends to address these gaps. Thus, this study aimed to describe healthcare professionals’ experiences with Learning from Excellence six months after its implementation in a postanaesthesia care unit. Methods A qualitative descriptive design was applied. Learning from Excellence was implemented in a postanaesthesia care unit of a Norwegian university hospital between November 2022 and May 2023. Six semi-structured focus group interviews were conducted, from May to June 2023, with a convenience sample of nurses (n = 17) and physicians (n = 7). The data were analysed through inductive reflexive thematic analysis. The study adhered to the COREQ guidelines. Results This study reports four prominent themes encapsulating healthcare professionals’ experiences with Learning from Excellence. These themes were termed as follows: 1) ‘Facilitates a more positive working climate’, including sub-themes ‘Helps spread positive feedback’ and ‘Feeling seen and motivated’; 2) ‘Why don’t I get any ‘likes’?’; 3) ‘Organisational learning is challenging’, including sub-themes ‘Hesitating to report’ and ‘Provides mostly superficial learning’; and 4) ‘Success inspires quality improvement project’. Conclusions Implementing LfE mostly contributed to a positive working climate in a postanaesthesia care unit. For LfE to be worth implementing, it is essential to improve organisational learning, while minimising the negative effects of LfE, such as exclusivity issues. Trial registration ClinicalTrials.gov NCT05794490; first registered on March 4, 2023.